Effects of Concentrate Feed Starch Source Offered Twice a Day on Feed Intake and Milk Production of Cows During the Early Postpartum Period - Rodrigo I. Albornoz; Victoria M. Russo; Christie K. M. Ho; Khageswor Giri; Michael S. Allen; Adam L. Lock; William J. Wales; Matthew I. Knight (Animals)
This experiment determined the effects of two different starch sources when offered twice a day to cows during the early postpartum period (1 to 23 d postpartum, treatment period) on dry matter intake (DMI), feeding behavior, and milk production. The subsequent effects on milk production in the carryover period (24 to 72 d) where cows received a common diet (grazed perennial ryegrass pasture plus concentrate supplements) were also measured. Thirty-two multiparous dairy cows were offered concentrate feed (8 kg DM/d) containing 5 kg DM of crushed wheat grain or ground corn grain (7 h in vitro starch digestibility of 65.8% and 58.8%, respectively). At each milking (morning and afternoon), cows were offered half of the concentrate feed, and upon return to their individual stalls, they were offered perennial ryegrass pasture silage (56.2% neutral detergent fiber (NDF), 39.8% acid detergent fiber (ADF), 16.6% crude protein (CP)) at 130% of their expected daily intake. Dry matter intake, milk yield, and body weight were recorded daily. Blood and milk sampling, body condition score, and feeding behavior measurements were performed weekly during the treatment period. During the carryover period, milk sampling and body condition score measurements were conducted on a weekly and fortnightly basis, respectively. In the treatment and carryover periods, there was no significant effect of starch source treatment on DMI, milk yield, milk composition, change in body weight, or body condition. Similarly, the starch source did not affect the concentrations of blood markers of energy status or inflammatory response. Despite differences in the in vitro starch fermentability between treatments, the starch source did not significantly affect production responses. It is possible that the elevated NDF and ADF concentrations of the forage offered during the treatment period, the limited difference in starch fermentability between treatments, and the temporal supply of fuels to the liver when starch sources were offered twice a day may have offset the effects of the type of starch source on DMI and production via physical signals associated with rumen fill and distention.